Omics in IgG4-related disease - Shaozhe Cai; Yu Chen; Ziwei Hu; Shengyan Lin; Rongfen Gao; Bingxia Ming; Jixin Zhong; Wei Sun; Qian Chen; John H Stone; Lingli Dong; Xiangxiang Pan (Chinese Medical Journal)
Abstract. Research on IgG4-related disease (IgG4-RD), an autoimmune condition recognized to be a unique disease entity only two decades ago, has processed from describing patients’ symptoms and signs to summarizing its critical pathological features, and further to investigating key pathogenic mechanisms. Challenges in gaining a better understanding of the disease, however, stem from its relative rarity—potentially attributed to underrecognition—and the absence of ideal experimental animal models. Recently, with the development of various high-throughput techniques, “omics” studies at different levels (particularly the single-cell omics) have shown promise in providing detailed molecular features of IgG4-RD. While, the application of omics approaches in IgG4-RD is still at an early stage. In this paper, we review the current progress of omics research in IgG4-RD and discuss the value of machine learning methods in analyzing the data with high dimensionality.